Setting the Stage for Youth-Led Devised Theatre for Social Change: Reflective Collaborative Inquiry on "Act Out Justice". Issue 3 (18th March 2022) - Horn, Elizabeth Brendel; Caine, Brittany; Cary, Maria; Freeman, Emily
Abstract: This study analyzes "Act Out Justice" (AOJ), a youth theatre for social change initiative of Orlando Repertory Theatre and the University of Central Florida. Employing AOJ's model of reflective collaborative inquiry (Horn et al., 2020 ), this article dramatizes the practice of responding to one's own work. Through narrative and dialogical reflection, four leaders of AOJ identify four challenges within the 2018–2019 programming: "building relationships, identifying social justice topics, accessing prior knowledge, and determining the audience demographic" (Horn et al., 2020, p. 378). Using reflective collaborative inquiry, the authors solidify programmatic changes in response to these challenges. This article illustrates the evolution of Act Out Justice as it relates to other theatre for social change work with young people and explores new modes for dialoguing, reflecting, and making programmatic changes.